Springback Analysis For Land Width Optimization In Cold Drawing Process Of Square Sectional Seamless Tubes - Dr. D.B. Karanjule, Dr. S. S. Bhamare (International Journal of Advanced Science and Technology, 2020)
Seamless tubes manufacturing process by cold drawing process achieves outer diameter, inner diameter and thickness of the tubes as per requirement. This paper emphasizes on the problem of springback effect on square cross sectional seamless steel tubes faced in the production with different land widths. The experimental study is carried for the analysis and modification on land width or bearing length of the die in controlling the springback of square sectional seamless steel tubes. This study deals with the effect of land widths of 5, 10, 15 and 20 mm on springback by conducting experimentation and finite element analysis using ANSYS. The results of this study reveals that 10 mm is optimum land width to minimize springback in square sectional tubes. This research improved springback results with the aid of series of experimentation. The results of this study reduced the rejection of precision tubes by 3 % saving substantial and considerable amount of the cold drawing manufacturing industry.